The urban land question : management and access for the urban poor in post apartheid South Africa - Mammon, Nisa (Department of Environmental and Geographical Science, 2015)
The premise of the thesis is that the developmental use of urban land should be ethical, fair and promote social justice. Using multiple research approaches and mixed methods this thesis examines the urban land question in South Africa and particularly Cape Town where land distribution and ownership are inequitable. The thesis unpacks land redistribution, land tenure reform and land restitution within this context. It is argued that the South African Constitution commits government to protect the property rights of those who currently own property and at the same time redistribute land to those who have been dispossessed and explores what this tension means for urban land redistribution and reform using the freedoms approach developed by Amartya Sen as a conceptual framework and as alternative to the neo-classical model. The main findings of the thesis can be summarized as follows. a) The thesis demonstrates that there is no logical reason why the freedoms approach cannot be extended to include urban land. b) The entitlements and endowments that urban land could bestow on the urban poor are shaped by how the State invests in land through the instruments of land planning and land use management which call for a significant role for the State as custodian of public land to not only make explicit the land asset register under public ownership but also instill trust in the poorer sectors of urban society. c) A two track system of land planning and land use management may be more appropriate in the post apartheid South African city, one stream for market driven land and one for targeted public land programmes that directly address urban poverty provided that the State is able to make strong connections between the philosophical and the technical aspects of land and land use management systems. d) As a two track system is suggested the land use management system requires to be reframed. To facilitate land redistribution and reform in urban areas of South Africa therefore, the thesis suggests that a deliberative and systemic planning approach needs to be adopted that is intervention focused. Only when the State assumes a more critical interventionist role in public land programmes would it be possible to obtain social justice and the principles of the good city in the South African urban context. e) Gaining access to and control over land resources beyond the market is possible but limiting for the majority of the urban poor when land and housing debates are conflated. This conflation results in other land debates being silenced yet these have the potential to offer alternatives to the neo-classical model of land and land use management as well as promote a wider role for public land than just housing.